GAMBARAN TINGKAT KECEMASAN WARGA DAERAH RAWAN BANJIR DI DUSUN TROBAKAL DESA KARANGREJO, KECAMATAN ARJOSARI, KABUPATEN PACITAN - Nur Afifah; Erika Dewi Nooratri (Jurnal Keperawatan Duta Medika, 2022)
Background; BPBD 2021 data states that natural disasters in Indonesia have reached 3,058 events. Floods dominate natural disasters that hit 1,288 events. Floods have a psychological impact in the form of anxiety disorders. Anxiety is an experience that is subjective, unpleasant, scary and worrying about the possibility of danger or the threat of danger. Anxiety can arise due to trigger factors such as natural disasters because everyone cannot predict when a disaster will come. Destination; assessing anxiety disorders in residents living in flood-prone areas using demographic data and the Hamillton Anxiety Rating Scale (HARS) questionnaire. Methods; This type of research is descriptive-quantitative. Sampling using purposive sampling technique with a total sample of 67 respondents. Data analysis using univariate analysis. Results; There was no anxiety as many as 3 people (4.5%), mild anxiety as many as 23 people (34.3%), moderate anxiety as many as 26 people (38.8%), severe anxiety 13 people (19.4%), very anxiety weight of 2 people (3.0%). Conclusion: Most of the residents who live in flood-prone areas experience anxiety disorders and most have moderate anxiety disorders